Variables socioeconómicas que explican la migración en Ecuador, Perú y Chile, 2009 al 2019. - Erazo Torres, Evelyn Eduvi; Ordoñez Luna, Kevin Andres (My University, 2022)
The present investigation reveals an analysis of the migration of people in Ecuador, Peru and Chile, which is a factor that has a great influence on the economy of countries around the world, because many people leave their homeland to live abroad for a short or long term. For this reason, a study was carried out with the objective of knowing and analyzing which are the most influential socioeconomic variables that affect the migration of these countries, in the period from 2009 to 2019. This research has been developed with a quantitative methodology, through the analysis of statistical data obtained from platforms such as the Central Bank of Ecuador and the INEC, applying the panel data method, which allowed us to verify the theories and generate conclusions that explain our research question and its objective. The results reflect that there is a cause and effect relationship between the GNI per capita variables and the life expectancy rate with migration. It is concluded that the increase in GNI per capita and life expectancy manage to reduce the departure of people from a country considering the differences between the economies studied.
La presente investigación da a conocer un análisis a la migración de personas en Ecuador, Perú y Chile, que es un factor que tiene una gran influencia en la economía de los países de todo el mundo, debido a que muchas personas abandonan su tierra natal para vivir en el extranjero por un corto o largo plazo. Por ello, se realizó un estudio con el objetivo de conocer y analizar cuáles son las variables socioeconómicas más influyentes que inciden en la migración de estos países, en el periodo del 2009 al 2019. Esta investigación se ha desarrollado con una metodología cuantitativa, mediante el análisis de datos estadísticos obtenidos de plataformas como el Banco Central del Ecuador y el INEC, aplicando el método de datos de panel, lo cual nos permitió verificar las teorías y generar conclusiones que explican nuestra pregunta de investigación y el objetivo de esta. Los resultados reflejan que si existe una relación causa y efecto entre las variables INB per cápita y la tasa de esperanza de vida con la migración. Se concluye que el incremento del INB per cápita y la esperanza de vida logran disminuir la salida de personas de un país considerando las diferencias existentes entre las economías estudiadas.
Keywords: MIGRACIÓN; EMIGRANTES; VARIABLES SOCIOECONÓMICAS